The Implementation of a Research-Based Learning Model to Motivate Students in Understanding Fungal Kingdom Concepts - Azizah, Istiqomah Nur; Julianti, Maritza; Aina, Tiara; Amalia, Evi; Wijayaningsih, Estu (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Biology learning is often considered difficult by students, especially on Fungal Kingdom concepts which involves abstract and complex concepts. This causes low student learning motivation. The study aimed to observe the application of a research-based learning model or Research-Based Learning (RBL) with a practicum method to motivate students in learning Fungal Kingdom concepts in class X. This study used a qualitative descriptive approach, with instruments in the form of observation sheets and written tests. The subjects of the study were students in grades X1, X2, and X3 at one of the public high school in Serang in the 2024/2025 Academic Year. Learning takes place following the RBL steps which include problem identification, hypothesis formulation, practicum implementation, discussion, data analysis, and evaluation. The results showed that 74.28% of students achieved scores above the minimum competion criteria with a class average of 82.78. This shows that the application of the RBL model with a practicum method can motivate students in learning Fungal Kingdom concepts. Students become more actively involved, enthusiastic in making observations, and show better understanding